Overlay removable partial dentures for a patient with ectodermal dysplasia: A clinical report - Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, E. T. (Mosby, Inc, 2001)
The orofacial characteristics of ectodermal dysplasia include anodontia or hypodontia, hypoplastic conical teeth, underdevelopment of the alveolar ridges, frontal bossing, a depressed nasal bridge, protuberant lips, and hypotrichosis. Patients with this disease often need complex prosthetic treatment. The options for a definitive treatment plan may include fixed, removable, or implant-supported prostheses, singly or in combination. However, financial constraints and other priorities can prevent patients from choosing the most desirable treatment. This clinical report describes the diagnosis and treatment of ectodermal dysplasia in an 18-year-old man. The treatment included interim removable partial dentures fabricated to establish an acceptable therapeutic occlusal vertical dimension, followed by definitive overlay removable partial dentures and composite restorations.